Transpulmonary thermodilution in patients treated with veno-venous extracorporeal membrane oxygenation - Loosen, Gregor; Conrad, Alice; Hagman, Michael; Essert, Nils; Thiel, Manfred; Lücke, Thomas; Krebs, Jörg (Annals of intensive care, 2021)
We tested the effect of different blood flow levels in the extracorporeal circuit on the measurements of cardiac stroke volume (SV), global end-diastolic volume index (GEDVI) and extravascular lung water index derived from transpulmonary thermodilution (TPTD) in 20 patients with severe acute respiratory distress syndrome (ARDS) treated with veno-venous extracorporeal membrane oxygenation (ECMO).
Gesehen am 20.06.2022